2022
DOI: 10.1007/s11524-021-00585-4
|View full text |Cite
|
Sign up to set email alerts
|

The Unequal Effects of Social Distancing Policy on Subway Ridership during the COVID-19 Pandemic in Seoul, South Korea

Abstract: In the Republic of Korea, social distancing policies relied on voluntary participation by citizens and exhibited short-term changes. In this situation, the effects of such policies varied depending on each community’s capacity to comply. Here, we collected subway ridership data for 294 stations on nine Seoul Metro lines and aggregated the data for each station to the 184 smallest administrative areas. We found that the mean percent change in subway ridership was fitted by an additive model of the log-transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…In El Paso, Texas, throughout the pandemic, recreational walking and use of green spaces was more greatly reduced in neighbourhoods with more deprivation than in less deprived neighbourhoods 34 . In Seoul, South Korea, the frequency of subway use during the pandemic decreased only in the least deprived areas, suggesting a disparity in the ability to sociallydistance by deprivation, similar to our own findings 35 . Our study, found stark disparities by deprivation status in activities undertaken such as working outside the home, use of public transport, and frequency of hospitality and leisure activities.…”
Section: Discussionsupporting
confidence: 90%
“…In El Paso, Texas, throughout the pandemic, recreational walking and use of green spaces was more greatly reduced in neighbourhoods with more deprivation than in less deprived neighbourhoods 34 . In Seoul, South Korea, the frequency of subway use during the pandemic decreased only in the least deprived areas, suggesting a disparity in the ability to sociallydistance by deprivation, similar to our own findings 35 . Our study, found stark disparities by deprivation status in activities undertaken such as working outside the home, use of public transport, and frequency of hospitality and leisure activities.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, high passenger volume was associated with the higher infection rate of destinations (e.g. bars, restaurants, and sport events) (Zhang et al 2021b) and the least deprived area (Ha et al 2022). It not only promotes the spread of virus to other parts of the city but also may lead to an outbreak in carriages (Hamidi and Hamidi, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Previous researchers have also tried to define pre- and post-COVID-19 pandemic criteria. For example, some marked the first occurrence of COVID-19 ( Milani, 2021 ; Mzoughi et al, 2020 ) or the first social distancing measures ( Ha et al, 2022 ; Kamga et al, 2021 ), but they did not have theoretical evidence of diving them. If future research develops a more scientific methodology to define the phases of the COVID-19 pandemic, it would be more helpful to understand the temporal dynamics of bike-transit relationships in the disastrous pandemic situation.…”
Section: Discussionmentioning
confidence: 99%
“…However, researchers have argued that the concrete separation of the pre- and post- COVID-19 periods is difficult due to the vagueness of specifying when the virus affects people's behavior ( Xin et al, 2021 ). Therefore, recent studies have considered social distancing policies and people's behavioral shifts in response to COVID-19 ( Ha et al, 2022 ; Kamga et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%